2017
DOI: 10.1080/2162402x.2017.1338239
|View full text |Cite
|
Sign up to set email alerts
|

EP4 Antagonism by E7046 diminishes Myeloid immunosuppression and synergizes with Treg-reducing IL-2-Diphtheria toxin fusion protein in restoring anti-tumor immunity

Abstract: Reprogramming of immunosuppressive tumor microenvironment (TME) by targeting alternatively activated tumor associated macrophages (M2TAM), myeloid-derived suppressor cells (MDSC), and regulatory T cells (Tregs), represents a promising strategy for developing novel cancer immunotherapy. Prostaglandin E2 (PGE2), an arachidonic acid pathway metabolite and mediator of chronic inflammation, has emerged as a powerful immunosuppressor in the TME through engagement with one or more of its 4 receptors (EP1-EP4). We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 47 publications
8
90
0
Order By: Relevance
“…Therefore, deletion of EP4 in myeloid cells resulted in a reduction of tumor burden in Apc Min/+ mice (130). An EP4 antagonist, E7046, has also been shown to shift TAMs from M2 to M1 macrophages and to enhance the antitumor effect of anti-CTLA-4 antibodies in syngeneic murine models of cancer (103). In vitro studies showed that PGE 2 promoted M2 macrophage polarization via a CREB/CRTC pathway in bone marrow-derived macrophages (131) and eliminates CD8 + T cells by inducing PD-L1 expression in TAMs (106).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, deletion of EP4 in myeloid cells resulted in a reduction of tumor burden in Apc Min/+ mice (130). An EP4 antagonist, E7046, has also been shown to shift TAMs from M2 to M1 macrophages and to enhance the antitumor effect of anti-CTLA-4 antibodies in syngeneic murine models of cancer (103). In vitro studies showed that PGE 2 promoted M2 macrophage polarization via a CREB/CRTC pathway in bone marrow-derived macrophages (131) and eliminates CD8 + T cells by inducing PD-L1 expression in TAMs (106).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Moreover, PGE 2 promoted tumor progression via inducing the development of MDSCs from bone marrow myeloid progenitor cells, whereas inhibition of PGE 2 signaling by deletion of EP2 or its antagonists blocked this differentiation in mice with implanted 4T1 murine mammary carcinoma tumors (102). An EP4 antagonist, E7046, has been shown to reduce tumor-infiltrating MDSCs and to enhance the antitumor effect of anti-CTLA-4 antibodies in syngeneic mouse models of cancer (103), indicating that EP4 mediates the effect of PGE 2 on MDSCs. An in vitro study showed that PGE 2 blocked differentiation of monocytes into DCs and promoted MDSC development (104).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…6A) (30). EP4 is the receptor for PGE2, an important transmembrane G protein-coupled receptor in macrophages (31). The results of the RT-qPCR analysis demonstrated that HFC-induced BMSCs significantly increased the expression levels of EP4 mRNA compared with RAW264.7 alone.…”
Section: Expression Of Genes Associated With Inflammation In Raw2647mentioning
confidence: 96%
“…Zhang et al also demonstrated that the expression of the M2 phenotype marker, Ym1, was decreased in the myeloid-specific EP4 knockout mice [52]. Albu et al reported that the EP4 antagonist, E7046, reduced M2-like macrophages [53]. Barminko et al also reported that EP4 signaling could induce the transition from M1 to M2 phenotype [54].…”
Section: Macrophagesmentioning
confidence: 97%